THE DETERMINATION OF SPECIFIC 228TH ACTIVITY IN SOIL - O. N. Prokof'ev (Радиационная гигиена)
The mineral fertilizer, wich have radioactive 228The, are bring into soil for increase of fertility. By biological chain soil-plant-man 228Th enter to man. This may lead to additional irradiation of man and to necessity of control of specific228Th activity in soil. The offered method allow to determine specific 228Th activity in soil.